1999
DOI: 10.1017/s0950268899002757
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Escherichia coli O157:H7 in range beef calves at weaning

Abstract: This study was designed to determine the prevalence of Escherichia coli O157:H7 infection of beef calves at weaning, prior to arrival at the feedlot or mixing with cattle from other sources. Fifteen range cow-calf herds, which weaned calves in October and November, were sampled in Kansas, Missouri, Montana, Nebraska and South Dakota. Faecal culture for E. coli O157:H7 was performed and anti-O157 serum antibody titres were determined by blocking ELISA. Thirteen of the 15 herds (87%) were found to have at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
119
2

Year Published

2000
2000
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 148 publications
(133 citation statements)
references
References 55 publications
12
119
2
Order By: Relevance
“…Isolation methods and time of year are the likely reasons for the difference between the results of this study and those previously reported. In other EHEC O157 studies, immunomagnetic separation and enrichment broth selection played a key role in the isolation of the target organism (8,12,21). In the absence of a reliable ''gold standard'' for the presence of EHEC O157 in samples, it is difficult to directly compare the methods used in this study with other culture techniques (8,12,21,22).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Isolation methods and time of year are the likely reasons for the difference between the results of this study and those previously reported. In other EHEC O157 studies, immunomagnetic separation and enrichment broth selection played a key role in the isolation of the target organism (8,12,21). In the absence of a reliable ''gold standard'' for the presence of EHEC O157 in samples, it is difficult to directly compare the methods used in this study with other culture techniques (8,12,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…In other EHEC O157 studies, immunomagnetic separation and enrichment broth selection played a key role in the isolation of the target organism (8,12,21). In the absence of a reliable ''gold standard'' for the presence of EHEC O157 in samples, it is difficult to directly compare the methods used in this study with other culture techniques (8,12,21,22). In addition, because operator experience can have a significant effect on the outcome obtained by different culture techniques, comparisons should be made on split samples in laboratories experienced in performing a given culture method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations